Changes of Phenolics, Condensed Tannins and Antioxidant Activity of Chinese Hickory (Carya cathayensis Sarg.) after Different Thermal Processing - He, Zhiping; Fu, Maorun; Mao, Linchun (Asian Journal of Chemistry, 2011)
To select the proper thermal treatments, changes of phenolic compounds, condensed tannins and antioxidant activities of methanol extracts from Chinese hickory kernels after different thermal processing were investigated. Total phenolic and condensed tannins were determined in all samples spectrophotometrically. Comparing with the raw materials, total phenolic of samples were reduced by 4.47, 7.37, 47.90 and 66.73 % and condensed tannins reduced by 33.65, 4.79, 46.23 and 69.94 % after roasting, microwave baking, boiling and pressured-steam heating treatment, respectively. Antioxidant activities of Chinese hickory were obviously decreased after boiling and pressured-steam heating, while little influence after roasting and microwaving. A strong correlations between total phenolic and reducing power, DPPH radical scavenging activities and superoxide anion scavenging activities (R2 = 0.9875, R2 = 0.9933, R2 = 0.8917, respectively) was observed. The results of this work indicated that Chinese hickory after roasting or microwave baking possesses higher functional benefit than other thermal processing to the view of nutrition.